2014
DOI: 10.5751/es-06947-190435
|View full text |Cite
|
Sign up to set email alerts
|

What does stakeholder involvement mean for fisheries management?

Abstract: ABSTRACT. The Common Fisheries Policy (CFP) sets the guidelines for the management of European fisheries. The CFP is revised every 10 years, and the last two revisions have laid the groundwork for extending stakeholder participation in European Union fisheries management. The fishery industry and nongovernmental organization (NGOs) especially are recommended to be given greater influence. In this paper we report results from an international survey on fisheries stakeholders' preferences for the three pillars o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 19 publications
(30 reference statements)
1
32
1
1
Order By: Relevance
“…This result demonstrates the awareness of the key role of ecological objectives, as in Janssen et al (2014), and also reflects the common sense of fishermen, who generally consider the spawners as the more fragile component of the stock, which necessitates protection. This is quite different from the results of Aanesen et al (2014), who found a low interest of the industry in fostering ecological objectives.…”
Section: Discussioncontrasting
confidence: 55%
See 2 more Smart Citations
“…This result demonstrates the awareness of the key role of ecological objectives, as in Janssen et al (2014), and also reflects the common sense of fishermen, who generally consider the spawners as the more fragile component of the stock, which necessitates protection. This is quite different from the results of Aanesen et al (2014), who found a low interest of the industry in fostering ecological objectives.…”
Section: Discussioncontrasting
confidence: 55%
“…Multi Criteria Decision Analysis (MCDA; e.g., Belton and Stewart, 2002) is an area of growing interest in fisheries management, and there are several applications worldwide (e.g., Soma, 2003;Leung, 2006;Bevacqua et al, 2009;Innes and Pascoe, 2010;Aanesen et al, 2014;Kavadas et al, 2015;Rossetto et al, 2015). MCDA models are powerful for addressing specific problems characterized by multiple and often conflicting objectives, something that is common in fishery systems.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The non-governmental organization (NGO) Oceana (oceana.org) published a report entitled Proposal for a responsible fishing in the Balearic Islands (Carreras and Cornax, 2011) in the form of five different leaflets including: (i) a global view of the local fisheries; (ii) recreational fisheries; (iii) small-scale fisheries; (iv) marine protected areas; and (v) bottom trawl fisheries. This material has also been analyzed and some proposals included in the RIP, which is therefore underpinned by the four main pillars of fisheries management (Aanesen et al, 2014;Röckmann et al, 2015): scientists, fishermen, policy-makers, and NGOs.…”
Section: Methods and Resultsmentioning
confidence: 99%
“…Identification of stakeholders for their involvement in the management process is not a straightforward task. Several authors defined the main stakeholder groups for the fishery sector (e.g., [25,26]). In this case, the four main stakeholder groups were identified and invited to participate in the execution of the DSC SMBTF.…”
Section: Functioning Of the Decision Support Conceptmentioning
confidence: 99%